2009
DOI: 10.1103/physrevb.80.155452
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopy in Si and C ion-implanted double-wall carbon nanotubes

Abstract: The effect of 170 keV Si and 100 keV C ion bombardment on the structure and properties of highly pure, double-wall carbon nanotubes has been investigated using resonance Raman spectroscopy. The implantations were performed at room temperature with ion doses ranging between 1 ϫ 10 13 ions/ cm 2 and 1 ϫ 10 15 ions/ cm 2 . As expected, the Si irradiation created more disorder than the C irradiation for the same ion fluence. For both species, as the ion-implantation fluence increased, the D-band intensity increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
(31 reference statements)
1
16
0
Order By: Relevance
“…We can see that the I D /I G ratio increases as the dose increases, thus confirming the increasing density of defects in the DWNT samples with increasing ion fluence. It is also clear that the I D /I G ratio depends strongly on the ion species used for the bombardment, as well as on the E laser used for characterization (Saraiva et al 2009).…”
Section: (A) the D Band In Swnt Bundlesmentioning
confidence: 99%
See 2 more Smart Citations
“…We can see that the I D /I G ratio increases as the dose increases, thus confirming the increasing density of defects in the DWNT samples with increasing ion fluence. It is also clear that the I D /I G ratio depends strongly on the ion species used for the bombardment, as well as on the E laser used for characterization (Saraiva et al 2009).…”
Section: (A) the D Band In Swnt Bundlesmentioning
confidence: 99%
“…For doses laser function versus ion fluence probed by two laser energies (open circle, E laser = 2.41 eV; filled circle, E laser = 2.54 eV) and (b) for Si and C ion bombardments. In (c) we plot the characteristic length L a for Si (filled circle) and C (filled square) implanted DWNT samples as obtained from the I D /I G intensity ratio using the model of Cançado et al (2008) and Saraiva et al (2009). larger than 40 × 10 13 ions cm −2 , the experimental data do not exhibit the E 4 laser dependence any more, and this is attributed to the very large density of defects which translates into a very small crystallite size L a . In this limit, the carbon lattice is likely to lose its sp 2 -like character, thus forming amorphous carbon and carbon clusters with a substantial amount of sp 3 bonding.…”
Section: (A) the D Band In Swnt Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in resistance due to deposition of ta-C may be attributed to two main factors, which are discussed below. One factor is the Cþ ion bombardment, which has been shown experimentally 13 and by simulation 27 methods to damage SWCNTs. However, the ion energies in the p-FCVA process (40-60 eV) are sufficient for penetration of at most 1-2 nm of the SWCNTN 12 and the evaporated carbon coated samples should be immune to the Cþ ion bombardment damage.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 99%
“…This loss of conductivity has been attributed to the damage of the SWCNT bundles due to high energy Cþ ion bombardment. 12,13 In our previous work, 14 we have shown that the high quality ta-C thin films can be deposited, using the pulsed filtered cathodic vacuum arc (p-FCVA) process on SWCNT networks. It was also observed that the ta-C deposited by the p-FCVA process, with a thickness of 20 nm on the SWCNT network, 14 provides sufficient mechanical protection, although the SWCNTN has an increase in the resistance similar to that observed by Schittenhelm et al 12 However, the SRIM simulations show that the penetration depth for even 100 eV Cþ ions in SWCNT networks (density around 1.33 g/cc) is around 1 nm, 12 while the typical ion energies in p-FCVA are around 40-60 eV.…”
Section: Introductionmentioning
confidence: 99%